ANALISIS YURIDIS PENETAPAN STATUS KELOMPOK KRIMINAL BERSENJATA DI PAPUA SEBAGAI TERORISME - Marinus Lase; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
At first the separatist movements that occurred in Papua were dealt with through the articles of treason in the Criminal Code (KUHP). However, on April 29, 2021, Coordinating Minister for Political, Legal and Security Affairs Moh. Mahfud MD, through Press Release No: 72/SP/HM.01.02/POLHUKAM/4/2021, stated that organizations and people in Papua who commit massive violence are categorized as terrorists. The determination of the KKB in Papua is not in accordance with the applicable positive law, so it does not provide legal certainty. This is because political motives in the Scope of Law Number 5 of 2018 considers criminal acts of terrorism not as political crimes. The purpose of this study is to determine how the status of armed criminal groups in Papua is determined as terrorism in Indonesian criminal law and to find out how the legal consequences of determining the status of armed criminal groups in Papua as terrorism.This type of research is normative legal research or library law research. This normative legal research is a study of the principle of legal certainty, where the government's policy in determining the status of armed criminal groups in Papua as terrorism does not provide legal certainty because the policy is not in accordance with the applicable criminal law. The data sources in this study consist of primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting data in this normative legal research used the literature review method. Based on the nature of this research which uses descriptive analytical research method, the data analysis used is a qualitative approach to primary data and secondary data.The determination of KKB in Papua as terrorism does not have legal certainty because the government's policy to include KKB in Papua in DTTOT is not in accordance with the applicable positive law. From a positive legal perspective, the government (Menko Polhukam) should not have the authority to declare a group in society as a terrorist group or organization and terrorism should not be considered a political crime. After the determination of the status of the KKB in Papua as terrorism, the legal consequence is that law enforcement against these groups will be different from law enforcement in general as regulated in the Criminal Procedure Code (KUHAP). The government in determining the status of the KKB in Papua as terrorism resulted in the government abusing its power and not based on applicable regulations. The legal consequences of determining the KKB in Papua as terrorism will make the KKB in Papua unable to be held criminally responsible.Keywords : KKB in Papua - Terrorism - Separatism - Political Crimes